Acute pancreatitis as first episode of pancreatic cancer: a report of 17 cases - WU Jingyi, LI Guojing, FEI Jian (Waike lilun yu shijian, 2020)
Objective To investigate the clinical features, diagnosis and treatment of pancreatic cancer with acute pancreatitis as first episode. Methods In this study we included 17 patients of pancreatic cancer with acute pancreatitis as first episode in our hospital from January 2008 to December 2018. Clinical data were reviewed retrospectively in terms of clinical presentation, diagnosis and treatment. Results All the patients were admitted to hospital diagnosed as mild acute pancreatitis. Clinical manifestations were recurrent acute abdominal pain mostly. Laboratory tests showed that tumor mar-kers elevated especially CA199. Pancreatic mass and pancreaticobiliary dilatation were shown by imaging. The patients were diagnosed pathologically through surgery. Pancreatic ductal adenocarcinoma was in 11 cases, hepatic metastatic adenocarcinoma in 2 cases. Four cases were diagnosed as adenocarcinoma by fine needle aspiration biopsy. Comprehensive treatment was performed mainly with surgery including duodenopancreatectomy in 5 cases, resection of pancreatic body and tail in 4 cases, total pancreatectomy in 2 cases, resection of metastatic hepatic lesion in 1 case, and cholecystectomy with hepatic biopsy in 1 case. Conclusions Patients with acute pancreatitis should be cautioned to the possibility of presence of pancreatic cancer. Comprehensive consideration is suggested through medical history reviewed combined with laboratory and imaging examination for the purpose of diagnosis and treatment as early as possible.